The maps of meaning consciousness theory - Andersen, Scott (Frontiers in Psychology, 2024)
In simple terms, consciousness is constituted by multiple goals for action and the continuous adjudication of such goals to implement action, which is referred to as the maps of meaning (MoM) consciousness theory. The MoM theory triangulates through three parallel corollaries: action (behavior), mechanism (morphology/pathophysiology), and goals (teleology). (1) An organism’s consciousness contains fluid, nested goals. These goals are not intentionality, but intersectionality, via the Darwinian byproduct of embodiment meeting the world, i.e., Darwinian inclusive fitness or randomization and then survival of the fittest. (2) These goals are formed via a gradual descent under inclusive fitness and are the abstraction of a “match” between the evolutionary environment and the organism. (3) Human consciousness implements the brain efficiency hypothesis, genetics, epigenetics, and experience-crystallized efficiencies, not necessitating best or objective but fitness, i.e., perceived efficiency based on one’s adaptive environment. These efficiencies are objectively arbitrary but determine the operation and level of one’s consciousness, termed as extreme thrownness. (4) Since inclusive fitness drives efficiencies in the physiologic mechanism, morphology, and behavior (action) and originates one’s goals, embodiment is necessarily entangled to human consciousness as it is at the intersection of mechanism or action (both necessitating embodiment) occurring in the world that determines fitness. (5) Perception is the operant process of consciousness and is the de facto goal adjudication process of consciousness. Goal operationalization is fundamentally efficiency-based via one’s unique neuronal mapping as a byproduct of genetics, epigenetics, and experience. (6) Perception involves information intake and information discrimination, equally underpinned by efficiencies of inclusive fitness via extreme thrownness. Perception is not a ‘frame rate’ but Bayesian priors of efficiency based on one’s extreme thrownness. (7) Consciousness and human consciousness are modular (i.e., a scalar level of richness, which builds up like building blocks) and dimensionalized (i.e., cognitive abilities become possibilities as the emergent phenomena at various modularities such as the stratified factors in factor analysis). (8) The meta dimensions of human consciousness seemingly include intelligence quotient, personality (five-factor model), richness of perception intake, and richness of perception discrimination, among other potentialities. (9) Future consciousness research should utilize factor analysis to parse modularities and dimensions of human consciousness and animal models.